Acute intermittent porphyria caused by defective splicing of porphobilinogen deaminase RNA: a synonymous codon mutation at -22 bp from the 5' splice site causes skipping of exon 3. Issue 5 (May 1996) - Llewellyn, D H; Scobie, G A; Urquhart, A J; Whatley, S D; Roberts, A G; Harrison, P R; Elder, G H
Abstract : Acute intermittent porphyria (AIP) results from mutations in the porphobilinogen deaminase (PBG) gene. Three of 14 randomly selected, unrelated patients with the cross reacting immunological material (CRIM) negative form of AIP were found to have previously undescribed RNA splicing defects. Defective splicing of exons 12 and 13 was caused by a C-->G transversion at position -3 of the 3' splice site of intron 11 and a G-->A transition at the first position of intron 13, respectively. Defective splicing of exon 3 was associated with a synonymous codon mutation (CGC-->CGG, R28R) at position -22 from the 5' splice site. Our findings are consistent with previous reports indicating that about 15% of mutations in the PBG deaminase gene that cause AIP affect RNA splicing and add to the evidence that synonymous intraexonic codon mutations may cause disease.